Instabilities and Robust Control in Fisheries - Anastasios Xepapadeas; Catarina Roseta-Palma (Fondazione Eni Enrico Mattei (FEEM), 2003)
Demand and supply analysis in fisheries often indicates the presence of instabilities and multiple equilibria, both in open access conditions and in the socially optimal solution. The associated management problems are further intensified by uncertainty on the evolution of the resource stock or on demand conditions. In this paper the fishery management problem is handled using robust optimal control, where the objective is to choose a harvesting rule that will work, in the sense of preventing instabilities and overfishing, under a range of admissible specifications for the stock recruitment equation. The paper derives robust harvesting rules, leading to a unique equilibrium, which could be used to design policy instruments such as robust quota systems.
Keywords: Q22; D81; 330; Fishery Management; Multiple Equilibria; Instabilities; Robust Control; Robust Harvesting Rules; Fischerei; Kontrolltheorie